Trends of long-term fluctuations of atmospheric humidification of the growing season in the steppe zone of Northern Kazakhstan - Kusainova Aisulu; Mezentseva Olga; Tusupbekov Zhanbolat (E3S Web of Conferences, 2024)
Agriculture is an important industry in Kazakhstan that ensures the stability of economic development. Within the northern regions of the republic, crop production received special development.The relevance of studying the impact of long-term fluctuations in precipitation on crop yields increases taking into account the projected trends in climate change in the modern period. The high natural heat supply of the territory during the growing season, along with the low availability of moisture resources, is a deterrent to the intensive development of the agro-industrial complex. The territory of Northern Kazakhstan as a whole is characterized by insufficient humidification during the warm period. However, there are wet years with rare recurrence, when moisture can be increased. The article considers the peculiarities of the change in the amount of atmospheric precipitation of the growing season for the long-term period 1961-2020 years according to weather stations located within the steppe zone of Northern Kazakhstan. The degree of aridization of territories was established on the basis of an analysis of the nature of changes in linear trends over different intervals.